IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA KETERAMPILAN PROSES SAINS MATERI EKOLOGI PADA SISWA SMPN 1 TARIK - Kiki Rohmatul Ula; Yuliani Yuliani; Akhmad Kurniawan (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Students’ abilities in science lessons is still low expecially in process skills of problem solving. Problems based learning model is one of the ways to overcome the problem. This research aim to determine the science process skills in in learning ecology material on environmental pollution sub-chapter in the 7th grade of problem based learning . The study used in this research is mixed method research with sequential explanatory design on 32 sample of SMPN 1 Tarik students. Data collection was done using observation sheet of science process skills, test sheet, and student response sheet. The analysis results obtained in terms of test score for each KPS indicator showed an 81%increase in student learning outcome. The increase in KPS indicator with applied problem-based learning model was 71% for hypotheses, 78% for concluding, 70% for communicating, and 72% for analizing with expert criteria. The students response to the problem based learning model reached 78% with good criteria. The conclusion is that there is an effect of increasing students’ scientific process skills by implementing of the problem-based learning model.